2018
DOI: 10.1016/j.msksp.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Referral to specialist physiotherapists in the management of whiplash associated disorders: Perspectives of healthcare practitioners

Abstract: Results support the feasibility of referral to specialist physiotherapists despite limited uptake in practice and recognised barriers to referral. These findings have implications for further study and adopting strategies to facilitate effective implementation and translation of the proposed pathway into primary care practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
10
2
Order By: Relevance
“…Similarly, use of the website appeared to improve actual practice of specialist HCPs through the promotion of a shared care approach in managing people with WAD at medium and high risk of nonrecovery. This is in contrast to the results of a previous study where the same group of specialist HCPs preferred to provide direct treatment (60%) over shared care (22%) [43]. A shared care approach in management was perceived by primary HCPs to facilitate the referral process and recovery for people with WAD [43].…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Similarly, use of the website appeared to improve actual practice of specialist HCPs through the promotion of a shared care approach in managing people with WAD at medium and high risk of nonrecovery. This is in contrast to the results of a previous study where the same group of specialist HCPs preferred to provide direct treatment (60%) over shared care (22%) [43]. A shared care approach in management was perceived by primary HCPs to facilitate the referral process and recovery for people with WAD [43].…”
Section: Discussioncontrasting
confidence: 83%
“…This is in contrast to the results of a previous study where the same group of specialist HCPs preferred to provide direct treatment (60%) over shared care (22%) [43]. A shared care approach in management was perceived by primary HCPs to facilitate the referral process and recovery for people with WAD [43]. The strategies used to engage specialist HCPs along with the interactivity of the website may have contributed to the improvements in practice observed.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Further, results of a study among injured workers showed that mandated risk assessment and early referral to psychologists of those at high-risk of delayed recovery improved outcomes and reduced costs [ 85 ]. A qualitative study exploring the perceptions of health professionals on WAD specialist referral also suggested that a standardised process for specialist review mandated by the insurers might promote good referral practices [ 86 ]. Another strategy could be to use WAD-specific standard reporting and referral forms, a strategy shown to improve compliance in other health populations [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%